Partição dos recursos florais de Byrsonima sericea DC por abelhas coletoras de óleo na restinga - Carpim, Camila Silva (2019)
Abstract 1. Byrsonima sericea DC (Malpighiaceae) is an important source of oil for restinga bees. Oil-collecting bees are specialized in harvesting oil, which is essential for their survival and persistence. 2. We assumed that the coexistence of oil-col